The Institutional Market and PNAE: revealing aspects underlying the local implementation process - Bastos, Rosária Cal; Freitas, Alair Ferreira de; Loreto, Maria das Dores Saraiva de; Paes, Luana Fernandes Silva (Argumentum, 2022)
The Brazilian government is formulating and implementing public policies that seek to encourage the consumption of food from the agricultural sector and to contribute to the insertion of family farming into the institutional market, as in the case of the National School Food Programme (PNAE). Based on this premise, this article analyses the process of implementing the PNAE in the city of Coimbra - MG, revealing local actors, networks, and social interactions. Based on the framework of the new economic sociology, this qualitative study makes use of documentary research, interviews with actors from the public sector and civil society, and observation. The results indicate that the PNAE in the municipality studied is characterised by the flexibilization of the dynamics of social networks and by collaboration and integration among the actors, with mutual assistance and sharing of actions.